Phonological Fossilization in Second Semester Modern Languages Students at the University of Quindío (2016)
The current research aimed mainly at finding the aspects that affect students’ pronunciation as well as the causes of phonological fossilization in modern languages students at the University of Quindío. This study was carried out in a second semester group. Fifteen students participated in the research, they were observed in their different classes during one month and their opinions about the topic were heard in a focus group. This research is considered as an ethnographic research specifically a case study because of its qualitative nature. The data were collected through observations, interviews and a focus group. The findings of the study indicated that the causes of phonological fossilization are: the absence of correction and feedback what leads to the lack of awareness by students of the difficulties they have regarding pronunciation, the differences between English and Spanish regarding phonetics, the non- inclusion of a phonetics course in lower semesters, dearth of proficiency level of the professors, the use of non-authentic materials, and the omission of an approach to teach pronunciation.